Solar temperature control device - WANG AIMING (2015)
The utility model provides a solar temperature control device. The device comprises a thermal insulation water tank, a heating radiator set, a solar thermal collector and a control unit, wherein a water circulating circuit is formed between the thermal insulation water tank and the solar thermal collector through a first circulating pump, a water circulating circuit is formed between the thermal insulation water tank and the heating radiator set through a second circulating pump, the solar thermal collector is connected with an external water source through an electromagnetic valve, a first temperature monitor is connected to the interior of the solar thermal collector, a second temperature monitor and a floating ball level switch are arranged in the thermal insulation water tank, an indoor temperature monitor is arranged in a workshop, and the electromagnetic valve, the two circulating pumps and the three temperature monitors are all connected with the control unit. According to the device, water in the water tank can be heated through solar energy, the temperature in the workshop is controlled through heat generated by circulating hot water, and sustainable development of resources is facilitated.